CURRENT STATUS OF CANINE BRUCELLOSIS IN INDIA - JASROTIA, NANCY; GULAGI, NAGARAJ; PATRA, MANAS KUMAR; KUJUR, ANJU (The Indian Journal of Animal Reproduction, 2021)
Canine brucellosis is a bacterial disease caused by Brucella canis which is the most common cause of reproductivefailure in dogs. Incidence of the disease is higher in stray dogs than in pets. Though brucellosis was reported to haveexisted in India since 1879, the methodical study was taken up as late as 1943, in animals and man in Madraspresidency. However, contagious abortion in livestock associated with brucellosis was first investigated in India by theImperial Veterinary Research Institute, Mukteshwar in 1918. Since then the disease has been reported almosteverywhere in India. Data on the prevalence of canine brucellosis in India is scarce or rather unreported, and thepublic health significance is not much known. Routine sero-surveillance of canines should also be done so thatproper control measures can be taken.
Keywords: Canine brucellosis; re-emerging anthropozoonosis; infertility; bacterial culture; prevalence